PROFIL TERAPI DAN EFEKTIVITAS PENGGUNAAN NIKARDIPIN PADA PASIEN STROKE HEMORAGI DI RSUD DR. ISKAK TULUNGAGUNG - Dimas Setyadi Putra; Dimas Setyadi Putra; Aghnia Fuadatul Inayah; Wella Kumalasari (Universitas Muhammadiyah Klaten, 2025)
Hemorrhagic stroke is a condition when brain’s blood vessels rupture and causes brain’s bleeding. This occurrence generates less blood supply to the brain which would drive cell death. Nicardipine is a CCB (Calcium Channel Blocker) antihypertensive drug that is used as a first-line intravenous drug to control hypertension in acute stroke patients when oral antihypertensive drugs are ineffective. This study aims at determining the effectiveness of nicardipine to reduce blood pressure in hemorrhagic stroke patients at Dr. Iskak Tulungagung Hospital. The current research adopted quantitative study by using a pre experiment design one group pre test-post test. The data was analyzed by using the Paired-Sample T Test through SPSS version 25 to determine the differences in blood pressure reduction. The current research is a retrospective study because the researcher identified Health Medical Record (Rekam Medik Kesehatan, RMK) data of 68 hemorrhagic stroke patients at Dr. Iskak Tulungagung Hospital from January - December 2020 period. The majority of the 62 (91%) patients as given medical therapy with nicardipin (0.5mcg/kgBB/minute) iv drips. The result shows that 66 patients (97%) are in the good condition when they have been discharged from the hospital. The study revealed a decrease in systole and diastole blood pressure in hemorrhagic stroke patients. The patient who was given nicardipine therapy at 0.5 mcg/kg/minute obtained systole p=0.000 and diastole p=0.000. Moreover, the patient who was threatened with nicardipine 1 mcg/kg/minute gathered systole p=0.000 and diastole p=0.008 with p<a (0.05). The outcome indicated that nicardipine effectively reduces blood pressure in hemorrhagic stroke patients in Dr. Iskak Tulungagung Hospital.